2017
DOI: 10.3389/fmicb.2017.02618
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Viable Soil Defined Media Using Quantitative Metabolomics Analysis of Soil Metabolites

Abstract: Exometabolomics enables analysis of metabolite utilization of low molecular weight organic substances by soil bacteria. Environmentally-based defined media are needed to examine ecologically relevant patterns of substrate utilization. Here, we describe an approach for the construction of defined media using untargeted characterization of water soluble soil microbial metabolites from a saprolite soil collected from the Oak Ridge Field Research Center (ORFRC). To broadly characterize metabolites, both liquid chr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 41 publications
0
35
3
Order By: Relevance
“…Likewise, similar to studies of root-associated metabolites [27][28][29], we too observed hydroxycinnamic acid derivatives, flavonoids, triterpenoids and other organic acids. Annotatable metabolites detected in our study differed significantly from annotatable metabolites described in prior untargeted analyses of agricultural soils [13,14], likely due to differences in metabolite extraction and instrumental protocols. Overlapping metabolites between the study of agricultural soil by Jenkins et al [13] and this study include valine and adenosine.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Likewise, similar to studies of root-associated metabolites [27][28][29], we too observed hydroxycinnamic acid derivatives, flavonoids, triterpenoids and other organic acids. Annotatable metabolites detected in our study differed significantly from annotatable metabolites described in prior untargeted analyses of agricultural soils [13,14], likely due to differences in metabolite extraction and instrumental protocols. Overlapping metabolites between the study of agricultural soil by Jenkins et al [13] and this study include valine and adenosine.…”
Section: Discussioncontrasting
confidence: 59%
“…For example, Ladd et al developed an untargeted LC-MS/MS method to analyze polar metabolites from an Arctic soil core [12]. Swenson et al implemented hydrophilic interaction liquid chromatography (HILIC)-MS, across 20 arid biocrust samples from a USA national park, relating metabolite profile following a wetting event to microbial growth [2], while Jenkins et al studied the metabolite profile of a single soil sample collected from the Oak Ridge Field Research Center by HILIC chromatography [13]. In contrast, Hewavitharana et al used reversed-phase liquid chromatography to assess the impact of a plant pathogen disinfestation method on an orchard metabolome [14].…”
Section: Introductionmentioning
confidence: 99%
“…Here, R2A media was chosen as a generalist culture media. This media has been used to recover more than 300 phylogenetically diverse isolates from P. trichocarpa rhizosphere and endosphere samples, and so should permit co-culture of a large number of combinatorial strain mixtures within the microwell environment (40,41). While the YR343-GFP monoculture generated growth profiles across the array with relatively low variance (s 2 =3.55) according to final end-point fluorescence levels, mixed cultures generated a wider range of growth profiles, with final growth levels of higher variance (s 2 =17.55), indicating an impact due to the addition of the environmental isolates ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The various substrates were sterilized, and incubated at 24°C for 8 hours with a 20 ”m equimolar defined medium, encompassing a variety of chemical classes, among them amino acids, sugars, organic acids, and nucleotides (Jenkins et al, 2017). The sterility of the system was confirmed by plating an aliquot on LB plates, followed by a 3-day incubation.…”
Section: Methodsmentioning
confidence: 99%
“…A selection of different substrates (3 mm glass beads, 4 mm sand, 4 mm clay) was incubated with 50 times concentrated defined medium (50x DM, see: “Sorption test with defined medium” section, (Jenkins et al, 2017)) or with 0x DM (DM without carbon sources, but with vitamins and minerals) for 6 h at 23°C. The substrates were subsequently washed three times with water, to remove soluble metabolites.…”
Section: Methodsmentioning
confidence: 99%